Radio and X-ray monitoring of the accreting millisecond X-ray pulsar IGR J17591-2342 in outburst - Gusinskaia, N.V.; Russell, T.D.; Hessels, J.W.T.; Bogdanov, S.; Degenaar, N.; Deller, A.T.; Van Den Eijnden, J.; Jaodand, A.D.; Miller-Jones, James; Wijnands, R. (OXFORD UNIV PRESS, 2020)
© 2019 The Author(s). IGR J17591-2342 is a new accreting millisecond X-ray pulsar that was recently discovered in outburst in 2018. Early observations revealed that the source's radio emission is brighter than that of any other known neutron star low-mass X-ray binary (NS-LMXB) at comparable X-ray luminosity, and assuming its likely >~6 kpc distance. It is comparably radio bright to black hole LMXBs at similar X-ray luminosities. In this work, we present the results of our extensive radio and X-ray monitoring campaign of the 2018 outburst of IGR J17591-2342. In total, we collected 10 quasi-simultaneous radio (VLA, ATCA) and X-ray (Swift-XRT) observations, which make IGR J17591-2342 one of the best-sampled NS-LMXBs. We use these to fit a power-law correlation index β = 0.37+0.42-0.40 between observed radio and X-ray luminosities (LR α LXβ ). However, our monitoring revealed a large scatter in IGR J17591-2342's radio luminosity (at a similar X-ray luminosity, LX ~1036 erg s-1, and spectral state), with LR ~ 4 × 1029 erg s-1 during the first three reported observations, and up to a factor of 4 lower LR during later radio observations. None the less, the average radio luminosity of IGR J17591-2342 is still one of the highest among NS-LMXBs, and we discuss possible reasons for the wide range of radio luminosities observed in such systems during outburst.We found no evidence for radio pulsations from IGR J17591-2342 in our Green Bank Telescope observations performed shortly after the source returned to quiescence. None the less, we cannot rule out that IGR J17591-2342 becomes a radio millisecond pulsar during quiescence.